Effects of Fuzheng Huayu recipe on entecavir pharmacokinetics in normal and dimethylnitrosamine-induced hepatic fibrosis rats - Tao Yang; Tian-Hui Zheng; Qiang Zhao; Wei Liu; Shu-Ping Li; Yan-Yan Tao; Chang-Hong Wang; Cheng-Hai Liu (Taylor & Francis Group, 2020)
Context Fuzheng Huayu recipe (FZHY) combined with entecavir (ETV) is used to treat the cirrhosis caused by chronic hepatitis B (CHB) infection. Objective To investigate the effect of FZHY on ETV pharmacokinetics under different conditions. Materials and methods A model of liver fibrosis was created by intraperitoneal injection of dimethylnitrosamine (DMN; 10 μg/kg) for 4 weeks in Wistar rats. Ultra-high-performance liquid chromatography-tandem mass spectrometry was used to determine the blood concentration of ETV. Pharmacokinetic characteristics of ETV (0.9 mg/kg) were investigated after co-administration with FZHY (0.55 g/kg) at certain time intervals in normal and model rats. Results The analytical method for ETV was validated at 0.5-50 μg/L with a correlation coefficient = 0.9996, lower limit of quantitation of 0.5 μg/L and mean accuracy of 104.18 ± 9.46%. Compared with the ETV-N group, the pharmacokinetic parameters of the EF-2 group did not change significantly, but that of the EF-0 group decreased in Cmax to 27.38 μg/L, in AUC0-t from 323.84 to 236.67 μg/h/L, and a delay in Tmax from 0.75 to 6.00 h; that of the EF-0 group presented a decrease in Cmax of 61.92%, delay in t1/2 of 2.45 h and delay in Tmax of 2.92 h. The t1/2e and Vd/F of ETV were increased significantly to 8.01 h and 24.38 L/kg in the ETV-M group. Conclusions The effects of FZHY on ETV pharmacokinetics were diminished with an increase of interval time. The best time to administer both drugs is >2 h apart.